Ifc 2002 annual report (international finance corporation, 2002)
IFAD is a specialized agency of the United Nations dedicated to eradicating poverty in the rural areas of developing countries. Seventy-five per cent of the world’s poorest people, 800 million women, men and children, live in rural areas. Most depend on agriculture to survive. IFAD works with poor rural people and their organizations, and other partners to develop solutions that enable poor rural people to overcome poverty themselves. We work with developing country governments, following their lead to design programmes and projects that fit within national systems and respond to the needs, priorities and constraints identified by poor rural people. We provide a mix of low-interest loans to governments and grants to support these development initiatives, and we ensure that lessons and experiences are scaled up to strengthen the agricultural and rural development policies and investments of our partner governments and the international development community.